Informally Self-Employed in Russia: Attitude to Formalization (On the Example of Saint Petersburg) - Tarando, E.E.; Malinina, T.B.; Nikiforova, O.A.; Sereda, V.M.; Pruel, N.A. (International Journal of Criminology and Sociology, 2022)
The paper examines the attitude to the formalization of informally self-employed in Russia on the example of the city of St. Petersburg. The authors proceeded from the position that this social group is heterogeneous, and different characteristics of representatives of this social group affect the attitude to the formalization of their economic activity. The negative attitude to formalization of representatives of this social group was revealed on the surface. However, this negative attitude among different subgroups of informally employed people turned out to be different. The results of the study show that different age groups of informally self-employed people react differently to government initiatives regarding registration of such activities. The presence or absence of social status in the sphere of formal employment, which many self-employed people combine with informal economic activity, proved to be a significant social characteristic in forming the attitude of the informally self-employed to formalization. Thus, the great value has stability of the institutional framework of formal self-employment generated by the state, and the state’s determination to follow its promises given to informally self-employed, so that this social group formalized its economic activity. It was found that a fairly large proportion of the informally self-employed took up a waiting attitude towards the state’s initiatives to formalize the economic activities of this social group. This paper will be useful for representatives of Russian state authorities who are developing measures of socio-economic policy in relation to informally self-employed citizens.